Fontes de distorções da rede geodésica Brasileira - Chaves, João Carlo [UNESP]; Dos Santos, Marcelo Carvalho; Nievinski, Felipe Geremia; Craymer, Michael R. (My University, 2008)
The Brazilian Geodetic Network started to be established in the early 40's, employing classical surveying methods, such as triangulation and trilateration. With the introduction of satellite positioning systems, such as TRANSIT and GPS, that network was densified. That data was adjusted by employing a variety of methods, yielding distortions in the network that need to be understood. In this work, we analyze and interpret study cases in an attempt to understand the distortions in the Brazilian network. For each case, we performed the network adjustment employing the GHOST software suite. The results show that the distortion is least sensitive to the removal of invar baselines in the classical network. The network would be more affected by the inexistence of Laplace stations and Doppler control points, with differences up to 4.5 m.
Distortions sources in the Brazilian geodetic network
Keywords: Adjustment; Brazilian Geodetic Network; Distortion; GPS; data quality; Doppler lidar; geodetic network; satellite data; triangulation; Brazil; South America